2002
DOI: 10.3171/jns.2002.97.4.0857
|View full text |Cite
|
Sign up to set email alerts
|

Organization of language areas in bilingual patients: a cortical stimulation study

Abstract: In this series, the authors found that bilingual patients could have common but also different cortical areas for both languages in temporoparietal areas and in frontal areas. In some cases, the authors found that language tasks such as counting, reading, or word retrieval in different languages can be sustained by language- and task-specific cortical areas. In bilingual patients, cortical mapping should ideally be performed using different language tasks in all languages in which the patient is fluent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
66
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 28 publications
9
66
1
Order By: Relevance
“…It is important to note that distinct Hebrew naming and reading sites were also found in areas distant from his first resection --such as in the middle frontal and angular gyri for naming and the supramarginal gyrus for reading. These results suggest that the distinct sites found for L2 are not solely due to the functional reorganization of the secondary language but represent the detection of genuine distinct sites that is consistent with other cortical stimulation studies of bilinguals 26,33,42,45,46,54 .…”
Section: Discussionsupporting
confidence: 76%
“…It is important to note that distinct Hebrew naming and reading sites were also found in areas distant from his first resection --such as in the middle frontal and angular gyri for naming and the supramarginal gyrus for reading. These results suggest that the distinct sites found for L2 are not solely due to the functional reorganization of the secondary language but represent the detection of genuine distinct sites that is consistent with other cortical stimulation studies of bilinguals 26,33,42,45,46,54 .…”
Section: Discussionsupporting
confidence: 76%
“…In an attempt to gain a better anatomical understanding of how multiple languages are represented in the human brain, Roux and Trémoulet [14 ]studied 12 bilingual patients who underwent surgery for brain tumours, during which they mapped cortical language sites by using electrostimulation. Strict overlapping of language areas (for all language tasks) was found in 5 patients, whereas the remaining 7 had at least one area that was language specific and sometimes task specific.…”
Section: Anatomical and Physiological Studiesmentioning
confidence: 99%
“…Previous studies of language areas in bilingual patients have found the cortical areas for multiple languages were located in the temporo-parietal cortex and in the frontal cortex with individual variability. 5,6,12,13) In the present patient, one of the language areas was located in the MITC. In various case series, naming sites in the temporal lobe were predominantly found in the superior and middle temporal gyri.…”
Section: Discussionmentioning
confidence: 95%
“…6) The language areas are located in the frontal and temporal cortices with individual variability in both monolingual patients and bilingual patients. 5,7,12,13) Furthermore, the presence of a language area in the inferior temporal cortex (ITC) is not usually detected by intraoperative mapping for glioma surgery as well as during the removal of other tumors and in epilepsy surgery. 10,12) We report a patient with unique language areas identified by intraoperative mapping.…”
Section: Introductionmentioning
confidence: 99%